Pembangkit Listrik Tenaga Mikro Hidro Di Lokasi Obyek Wisata Geopark Ciletuh Sukabumi - Hartono, Hartono; Candra Pertala, Erik; Sudarma, Ade (Jurnal Surya, 2022)
The Technology community service activity program that will be disseminated to the community is entitled Micro Hydro Power Plant at the Location of Ciletuh Sukabumi Geopark Tourism Objects. The location of this activity is the border of Ciwaru, Ciemas and Girimukti Villages, Ciemas District, Sukabumi Regency. The problem faced by partners as managers of Ciletuh Geopark tourism objects, especially Puncak Darma and Curug Cimarinjung, is the lack of electrical energy supply both at the location of tourist objects and in supporting facilities around the object and also the surrounding community. The method of solving the problems faced by this partner is to make a micro hydro power plant (PLTMH) installation with a gravity system and provide counseling and training. The result of this activity is that it is hoped that most of the managing community and the environment around the tourist object can get a supply of electrical energy that meets the needs of the management of tourism objects and their supporters. From the results of this activity, an electrical installation with a maximum capacity of 3000 watts was created.